BaptisteVandecrux/SEB_Firn_model: GEUS surface energy balance and firn model v0.3 - Vandecrux, Baptiste (Zenodo, 2021)
GEUS firn model as used in the article: Vandecrux, B., Colgan, W., Solgaard, A. M., Steffensen, J.P., Karlsson, N.: Firn Evolution at Camp Century, Greenland: 1966-2100, https://doi.org/10.3389/feart.2021.578978, 2021.